(untitled) (TAJ: Journal of Teachers Association, 2020)
Background: Traditionally in herniotomy, indirect hernial sac is dealt by high ligation and removal of the redundant part, to avoid recurrence. However, some authorities are of the opinion that excision of the hernial sac without ligation is not associated with recurrence of the hernia. Some have even shown adverse events related to hernial sac ligation like increased post-operative pain and discomfort. There is no consensus on how the hernial sac should be managed during laparoscopic herniotomy. Objectives: Present study aimed to determine the feasibility of laparoscopic sac excision without ligation in pediatric age group, by a randomized comparison. Materials and methods: This interventional study was performed in the department of Paediatric Surgery, Rajshahi Medical College Hospital, Rajshahi, Bangladesh, over a period of one year. A total of 189 patients were included in the study as per inclusion and exclusion criteria and randomized in the three groups. Comparisons were made among three procedures of laparoscopic herniotomy, namely; Percutaneous extraperitoneal closure, Intraperitoneal purse-string closure and laparoscopic sac excision without ligation. The main outcome measures were recurrence rate, operative time, hospital stay, postoperative hematoma and hydrocele formation. Results: Recurrence rate, operative time and hospital stay were not amplified in laparoscopic sac excision procedure than others. Postoperative hydrocele formation was significantly less. Conclusion: Laparoscopic sac excision in indirect pediatric inguinal hernia is safe. The procedure is not associate TAJ 2020; 33(2): 20-26